Rate of return - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Planning Agricultural Research: A sourcebook Edited by G Gijsbers, W Janssen, H Hambly Odame & G Meijerink, ISNAR, 2001. 363 pp. ISBN 0851994016 US$ 55 Euro 60.70 Stock number: ISNAR288